Rock mass geomechanical characterization by seismic methods: Poisson's ratio - TL Goh, A Ghani Rafek, Abdul Rahim Samsudin, . (2011)
he mechanical parameters such as Poisson ratio are input parameter for rock engineering especially in numerical modeling computer software. Seismic methods were utilized to determine Poisson's ratio for fresh (grade I), slightly weathered (grade II), moderately weathered (grade III) and highly weathered (grade IV) rock masses.